Investigation of the structural, optical and crystallographic properties of Bi2WO6/Ag plasmonic hybrids and their photocatalytic and electron transfer characteristics. Issue 27 (14th June 2019) - Kavinkumar, Veerappan; Verma, Atul; Masilamani, Sriramkumar; Kumar, Sanath; Jothivenkatachalam, Kandasamy; Fu, Yen-Pei
Abstract : We have fabricated an efficient Bi2 WO6 -Ag plasmonic hybrid via the photoreduction technique and the obtained materials were well characterized with sophisticated instruments. Abstract : Effective exploitation of visible-light unique structural and electronic properties has enormously attracted more researchers for photocatalytic systems. Here, we have fabricated an efficient Bi2 WO6 -Ag plasmonic hybrid via the photoreduction technique and the obtained materials were well characterized with sophisticated instruments. The BW-Ag-1 catalyst showed the maximum photocatalytic activity for the degradation of cationic dyes rhodamine B (RhB) and malachite green (MG) and the rate constant was 2.6 × 10 −2 min −1 and 1.6 × 10 −2 min −1 respectively, which is the highest among the synthesized catalysts. The enhanced photocatalytic activity could be ascribed to the synergistic effect of surface plasmon resonance caused by Ag NPs, which could enhance the photoabsorption capability, photon scattering, and plasmon resonance energy transfer, and plasmon-induced hot electron transfer (PHET) ensures better photocatalytic performance. In addition, we have evaluated the influence of Ag on Bi2 WO6 microspheres with crystallographic and morphological studies, which depict a negligible change in the crystal structure and an increase in the Ag (FCC) phase with an increase in AgNO3 content and the FE-SEM and mapping images disclose the uniform dispersion of Ag on the surface of Bi2 WO6 . Trapping experiments revealed that the active species for the degradation of MG were superoxide (˙O2 − ) radicals as the major reactive species with holes being the main instigative species, which are effectively involved in the photo-induced catalytic reaction. Furthermore, we have studied the effect of different pH of MG initial solution and the plasmonic hybrid catalyst depicted high stability and durability even after five successive cycles. In the electrochemical study, the BW-Ag-1 modified glassy carbon electrode (GCE) demonstrated a superior current density due to the redox behavior and smaller resistance revealing the addition of Ag NPs to be beneficial for the catalytic performance.